Odd Graceful Labelling of the Union of Cycle and Lobsters - JebaJesintha, J; Jayaglory, R; Bhabita, G (International Journal of Computer Sciences and Engineering, 2025)
Odd graceful labeling is one of the major evolving research areas in the field of graph labeling. It is defined as for any graph G with q edges if there is an injection f from V(G) to 0, 1, 2, …, (2q-1) such that, when each edge xy is assigned the label │f(x) ─ f(y)│,so that the edge labels are 1, 3, 5, …, (2q-1) then the graph G is said to be odd graceful. Graph labeling has a vast range of real life applications which has provided major contributions in the development of new technologies. In this paper we have investigated and proved that the graph G which is obtained by joining m isomorphic copies of lobster graph to each vertex of the cycle Cm admits odd graceful labeling.